A Theory of Compensation and Personnel Policy in Hierarchical Organizations with Application to the United States Military - Asch, Beth J.; Warner, John T. (Journal of Labor Economics, 2001)
A large literature attempts to explain compensation and personnel policies in large organizations. Three features of the U.S. military system—flat rank spreads in pay, a relatively generous pension, and heavy reliance on up‐or‐out promotions—are at variance with common practices in large civilian organizations. This article develops a model of individual decision making in a large, hierarchical organization and uses the model to explain these apparent puzzles. The lack of lateral entry and heterogeneity in entrants’ abilities and preferences for military service play key roles in the observed policies.